“L’anello che non tiene”: ai margini di un sistema ortografico - Riccardo Regis; Matteo Rivoira (Lengas)
This paper deals with the usage of three graphic systems, namely the orthographies known as “Pacotto-Viglongo”, “Classical” and “Escolo dóu Po”. While the first is generally used for writing the Piedmontese variety of Turin, the last two prove to be the most typical tool to write the Occitan varieties of Italy. We focus on how the above-mentioned graphic systems are applied to varieties or languages different from those they were originally planned for, highlighting and discussing some critical issues associated with these extended usages.